ANALISIS PERTUMBUHAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA DILIHAT DARI TINGKAT PENDIDIKAN DI KABUPATEN INDRAGIRI HILIR - Khairu Rahmadani; Harlen '; Hainim Kadir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aim of this study include: provide an overview of inventory and laborrequirements as well as provide an overview of the economic opportunitiesavailable as the foundation to move development of strategic sectors.Research carried out in the region Indragiri Hilir. Analysis of the presentcondition and future employment through employment elasticity analysis methods. For the data used in the context of this study is data from BPS.Results of research conducted showed that the economy Indragiri Hilir in2012 grew by 7.47% and employment growth of 4.14%, with elasticity of 0.54. So that the number of job opportunities in the year 2012 as many as 304 792 people. While economic forecasts Indragiri Hilir in 2015 grew by 7.72% and employment growth of 4.87%, with employment elasticity of 0.5363. Estimated GDP at constant 2000 prices Indragiri Downstream of Rp. 10012.91 billion and employment opportunities created as many as 342 002 people.Keywords: Labor, employment opportunities